Cloning and Expression of Staphylococcus Epidermidis AT2 Lipase in Yarrowia Lipolytica - Mohd Nooh, Hisham (2011)
Proteolytic degradation and the production of protein that accumulates as misfolded form always occur in bacterial expression system. In view of that, Yarrowia lipolytica is chosen as a host to express heterologous protein. The gene encoding sequence of Staphylococcus epidermidis AT2 lipase (1.2kb) was cloned into Y. lipolytica expression vector (pYLEX1) and placed under the regulation of the strong hybrid promoter (hp4d) carrying four tandem copies of an upstream activator sequence (UAS1B) from pXPR2 and a minimal pLEU2 fragment. Previously, primers were designed on the basis of S. epidermidis lipase precursor (geh1) gene (AF053006). PCR (Polymerase chain reaction) was used to amplify the gene and cloned into pJET 1.2/blunt-end vector (Fermentas) transformed into E. coli DH5α competent cell. After the gene was propagated in E. coli, the gene were purified and ligated into pYLEX1 vector (Yeastern Biotech). The recombinant plasmid was extracted and linearized before it was transformed into Y. lipolytica host strain Po1g. The recombinant Y. lipolytica was grown on YNB selection medium. Five positive transformants harboured the expected size of AT2 lipase gene were obtained and one of the transformants showed the highest expression. The expression of AT2 lipase enzyme was optimized at of 28 0C with the agitation speed of 200 rpm in optimized YNB medium. Process of breaking the cells or sonication profile was optimized at 7.5 min and the highest activity obtained was 14 U/mL. The crude proteins were electrophoresed on 12% (w/v) of SDS-PAGE and estimated protein band of 43 kDa was detected when stained with Coomassie brilliant blue. The expressed enzyme retained 100% of its activity after 30 min incubation (37 0C) in n-hexane, p-xylene and dimethyl sulfoxide.